Child Grooming Approach Model of Offenders toward Children on Social Media (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
Crimes against children are getting higher and more diverse. One of them that is currently rampant is the case of Child Grooming which targets children through the use of social media. This research aims to discuss how child grooming perpetrators approach child victims through social media. The online Child Grooming mode on social media is considered a mode that is quite widely used by perpetrators who are also children because perpetrators can easily trick victims virtually with different social media accounts. The theory used in this research is Space Transition theory. The research subjects were 3 child grooming offenders (X, Y, and Z) who were classified as children. This research uses qualitative method with descriptive analysis approach technique. The results showed that child grooming perpetrators use various approaches to approach their victims. The perpetrator will try to build a relationship to gain the victim’s trust. Afterward, the perpetrator will use his control so that the victim complies with the perpetrator’s wishes. After the victim is trapped by seduction and the perpetrator succeeds in committing sexual acts, the perpetrator will make threats with the aim that the victim is silent and wants to maintain a relationship with the perpetrator.